Income Management Strategies of Part-Time Working Students in Samarinda City - Latiffah, Ulia; Nurmanina, Agustin (Citra Media Publishing, 2025)
In recent years, the phenomenon of university students working part-time has become increasingly prominent in major Indonesian cities, including Samarinda. This trend reflects the socio-economic dynamics of urban communities that demand adaptation to the rising costs of living and education. This study aims to analyze the income management strategies of part-time working students by examining the types of employment, work motivation, spending patterns, and financial strategies they adopt. The phenomenon has grown alongside the expansion of job opportunities in the service and culinary sectors in Samarinda, encouraging students to participate in economic activities to meet their living and educational needs. This research employs a qualitative approach with primary data were collected through in-depth interviews with thirteen part-time students of the Social Development Program at Mulawarman University (cohorts 2021–2024), along with three supporting informants from their workplaces. The findings reveal that the most common types of part-time jobs among students include barista, cashier, waitress, receptionist, pastry shop attendant, and junior pastry chef. The main motivations for working part-time are financial necessity, gaining work experience, and fostering independence. Spending patterns show a prioritization of primary needs, education, and lifestyle, while income management strategies include basic financial literacy, recording income and expenses, and saving habits. Although students demonstrate a reasonable level of financial awareness, their money management practices remain relatively simple and unstructured. This study provides empirical contributions to the discourse on financial literacy and the economic behavior of part-time working students in urban contexts. Moreover, the findings offer valuable insights for educational institutions to design more practical and sustainable financial literacy support programs for students.